Fenomena Gaya Hidup Hedonisme di Kalangan Remaja dan Orang Dewasa dalam Relasi Teman Sebaya: Studi Kepustakaan: Studi Kepustakaan - Sri Rahayu; Aida Safitri; Risma Anita Puriani (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2026)
This research explores hedonistic lifestyle patterns as a social reality that grows within peer interactions, both in adolescence and adulthood. The investigation applies a qualitative descriptive literature review by examining national scholarly publications issued from 2016 to 2026. The findings indicate that hedonistic tendencies should not be interpreted merely as individual choices to seek enjoyment. Instead, they emerge from social processes shaped by interaction, peer influence, and shared norms that develop within a group. In this context, peer circles function as influential socialization agents, encouraging conformity so individuals can be accepted and avoid social exclusion. The study also identifies differences in underlying motivations across life stages. Among adolescents, hedonistic behavior is closely linked to identity exploration and self-definition. For adults, however, it is more associated with maintaining self-image, signaling social standing, and displaying markers of achievement. Overall, environmental dynamics, the expansion of consumer-oriented culture, and intensive exposure to social media play significant roles in strengthening this phenomenon in Indonesia.